Laser diode beam basics, manipulations and characterizations - Sun, Haiyin (SpringerBriefs in Physics, 2012)
Many optical design technical books are available for many years which mainly deal with image optics design based on geometric optics and using sequential raytracing technique. Some books slightly touched laser beam manipulation optics design. On the other hand many books on laser diodes have been published that extensively deal with laser diode physics with little touching on laser diode beam manipulations and characterizations. There are some internet resources dealing with laser diode beams. However, these internet resources have not covered enough materials with enough details on laser diode beam manipulations and characterizations. A technical book concentrated on laser diode beam manipulations and characterizations can fit in to the open and provide useful information to laser diode users. Laser Diode Beam Basics, Manipulations and  Characterizations is concentrated on the very practical side of the subject, it only discusses the basic physics and mathematics that are necessary for the readers in order to understand the subject. This book is intended to provide a practical guidance and reference to those scientists and engineers who are still new to laser diode applications, and to those undergraduate and graduate students who are studying lasers and optics. Readers are expected to be able to fast and easily find the most practical and useful information about laser diodes in this book without the need of searching through a sea of information.